2008
DOI: 10.1590/s0001-37652008000200016
|View full text |Cite
|
Sign up to set email alerts
|

Study of wet precipitation and its chemical composition in South of Brazil

Abstract: The purpose of this study is to analyze the chemical composition of wet precipitation in samples collected at three stations in the Candiota region in the Brazilian state of Rio Grande do Sul (RS). Samples were collected in 2004. Variables analyzed in wet precipitation were pH, conductivity, and concentration of Cl − , NO − 3 , SO 2− 4 F − , Na + , Ca 2+ , Mg 2+ , K + , NH + 4 , Cu, Zn, Fe, Mn, Pb, Ni, Cd, Co, and Cr. SO 2 and NO 2 distribution over the time were also evaluated. Results have showed that pH < 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
(40 reference statements)
2
11
1
3
Order By: Relevance
“…Table 7 compares the mean concentrations of these heavy metals to results from similar studies conducted in other countries. The results indicate that mean concentrations of Cu, Pb and Zn in our study are considerably below the reported concentrations in Ghore El-Safi (Jordan) [10] and Baghdad (Iraq) [35], but in comparison with the results from [35] Candiota region (Brazil) [34], the results of our study show higher concentrations. The differences among these three heavy metals concentrations may be due to both different regional conditions and different pollution control regimes followed in these countries.…”
Section: Cu Pb and Zn In Rainwatercontrasting
confidence: 90%
See 1 more Smart Citation
“…Table 7 compares the mean concentrations of these heavy metals to results from similar studies conducted in other countries. The results indicate that mean concentrations of Cu, Pb and Zn in our study are considerably below the reported concentrations in Ghore El-Safi (Jordan) [10] and Baghdad (Iraq) [35], but in comparison with the results from [35] Candiota region (Brazil) [34], the results of our study show higher concentrations. The differences among these three heavy metals concentrations may be due to both different regional conditions and different pollution control regimes followed in these countries.…”
Section: Cu Pb and Zn In Rainwatercontrasting
confidence: 90%
“…Metals with anthropogenic origin, especially Zn, show high concentration levels. These are controlled by the adsorption/ desorption processes of Fe and Mn oxides/hydroxides during precipitation [34]. Table 7 compares the mean concentrations of these heavy metals to results from similar studies conducted in other countries.…”
Section: Cu Pb and Zn In Rainwatermentioning
confidence: 99%
“…indicating its origin from earth crust. These findings of our study are in accordance with the results reported in earlier studies (Yusuf and Rashid, 1995;Banerjee, 2008;Teixeira et al, 2008).…”
Section: Metal Analysissupporting
confidence: 94%
“…Studies conducted in the Candiota region and other areas under the influence of the coal-fired power station have shown the presence of Cl particles (Braga et al 2004). The presence of Cl and Na from natural sources has been reported in other studies in the region (Teixeira et al 2008;Braga et al 2004).…”
Section: Seasonal Variation Of Chemical Elementsmentioning
confidence: 62%